2018
DOI: 10.1186/s12903-018-0618-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dynamic aging on the wear and fracture strength of monolithic zirconia restorations

Abstract: BackgroundThe purpose of this study is to evaluate the wear and fracture strength of crowns and three-unit partial fixed dental prosthesis (FDP) fabricated using by Bruxzir and Incoris TZI as recently introduced monolithic zirconia materials.MethodsA total of sixteen crowns and sixteen three-unit FDPs were fabricated using Bruxzir and Incoris TZI (n = 8). All specimens were subjected to a 2-body wear test in a dual axis chewing simulator for 1,200,000 loading cycles against steatite antagonist balls. The fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
36
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 32 publications
7
36
2
Order By: Relevance
“…Most of the studies evaluated flexural strength rather than fracture resintance [11,28,[30][31][32]. Similar to Stawarczyk et al [12], Flinn et al [28,30] Among the zirconia, as also observed in the present study, BruxZir was suggested to have superior physical properties and fracture resistance since it was indicated for patients with bruxism [29,35].…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Most of the studies evaluated flexural strength rather than fracture resintance [11,28,[30][31][32]. Similar to Stawarczyk et al [12], Flinn et al [28,30] Among the zirconia, as also observed in the present study, BruxZir was suggested to have superior physical properties and fracture resistance since it was indicated for patients with bruxism [29,35].…”
Section: Discussionsupporting
confidence: 73%
“…In contrast, in the present study, BruxZir and Prettau exhibited superior fracture resistance compared to Katana while occlusal wear area and volume were similar. Similarly, Sarikaya and Hayran, reported no fracture despite 5-year artificial aging in BruxZir and InCoris TZI zirconia material [29]. There was no fracture observed during the aging procedure in the present study either.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations